PENGARUH MODEL CASE BASED LEARNING DENGAN PENDEKATAN KEARIFAN LOKAL TERHADAP PENALARAN MATEMATIS - Fauzi, Asri; Ibrahim, Ibrahim; Rahmatih, Aisa Nikmah (Program Studi Pendidikan Matematika, 2025)
This study aimed to test the effect of a case-based learning model with a local wisdom approach on students' mathematical reasoning. This type of research is quasi-experimental research with a nonequivalent control group design. The place of this research is at the University of Mataram, the PGSD study program. The population of the study was 300 students in the second semester, while the sample used in this study was 120 students selected using a random sampling technique. The research instrument used a mathematical reasoning test. The data analysis technique used normality and homogeneity tests as prerequisite tests, and independent sample t-tests for hypothesis testing and finally used the N-Gain test. The results of this study showed that the data were normally distributed and homogeneous. Then, from the results of the hypothesis test, the significance. (2-tailed) value was obtained of 0.04 <0.05 so that H0 was rejected and Ha was accepted, meaning that there was a significant difference between the average mathematical reasoning of students in the control group and the experimental group so that it was concluded that there was an effect of the case-based learning model with a local wisdom approach on students' mathematical reasoning abilities. Meanwhile, the N-Gain test results obtained a score of 0.45 with moderate criteria. This means that the case-based learning model with a local wisdom approach has a moderate level of influence on students' mathematical reasoning abilities.